Periostin as a modulator of chronic cardiac remodeling after myocardial infarction - Minicucci, Marcos Ferreira [UNESP]; Santos, Priscila P. Dos; Rafacho, Bruna P.m.; Goncalves, Andrea F.; Ardisson, Lidiane P.; Batista, Diego F.; Gaiolla, Paula Schmidt Azevedo [UNESP]; Polegato, Bertha Furlan [UNESP]; Okoshi, Katashi [UNESP]; Pereira, Elenize J.; Paiva, Sergio A.r.; Zornoff, Leonardo Antonio Mamede [UNESP] (Universidade de São Paulo (USP), Faculdade de Medicina, 2013)
OBJECTIVE: After acute myocardial infarction, during the cardiac repair phase, periostin is released into the infarct and activates signaling pathways that are essential for the reparative process. However, the role of periostin in chronic cardiac remodeling after myocardial infarction remains to be elucidated. Therefore, the objective of this study was to investigate the relationship between tissue periostin and cardiac variables in the chronic cardiac remodeling induced by myocardial infarction. METHODS: Male Wistar rats were assigned to 2 groups: a simulated surgery group (SHAM; n = 8) and a myocardial infarction group (myocardial infarction; n = 13). After 3 months, morphological, functional and biochemical analyses were performed. The data are expressed as means±SD or medians (including the lower and upper quartiles). RESULTS: Myocardial infarctions induced increased left ventricular diastolic and systolic areas associated with a decreased fractional area change and a posterior wall shortening velocity. With regard to the extracellular matrix variables, the myocardial infarction group presented with higher values of periostin and types I and III collagen and higher interstitial collagen volume fractions and myocardial hydroxyproline concentrations. In addition, periostin was positively correlated with type III collagen levels (r = 0.673, p = 0.029) and diastolic (r = 0.678, p = 0.036) and systolic (r = 0.795, p = 0.006) left ventricular areas. Considering the relationship between periostin and the cardiac function variables, periostin was inversely correlated with both the fractional area change (r = -0.783, p = 0.008) and the posterior wall shortening velocity (r = -0.767, p = 0.012). CONCLUSIONS: Periostin might be a modulator of deleterious cardiac remodeling in the chronic phase after myocardial infarction in rats.
Keywords: Fibrosis; Myocardial Infarction; Periostin